Antimicrobial Sensitivity Pattern of the Common Uropathogens among Patients Admitted in A Tertiary Care Hospital in Bangladesh (Journal of Medicine, 2020)
Urinary tract infection is one of the most common bacterial infections seen in clinical practice both in developed and developing countries. The causative agents of Urinary tract infection vary from place to place and they also vary in their susceptibility and resistance patterns. This descriptive study aimed to evaluate the antibiotic susceptibility patterns of pathogens isolated from routine laboratory specimens at Dhaka Medical College Hospital. A descriptive cross- sectional study was done from January 2018 to June 2018. A total of 100 mid-stream urine samples from the suspected UTI patients were tested microbiologically and antimicrobial susceptibility test were performed for the isolated pathogens using Kirby-Bauer disk diffusion method with positivity rate of UTI was 90% (90/100). Escherichia coli (39%) was the most UTI causing bacteria followed by Klebsiella 18(18%), Acinetobacter 12(12%), Staphylococci, 9 (9%), Pseudomonas 6 (6%), Enterococcus species 3 (3%) and Proteus 3 (3%). Female 83 (83%) were more affected in comparison with male. Adult female especially age range 18-30 years were found in high risk. Nitrofurantoin, Amikacin and Meropenem were recorded as most sensitive antibiogram for most of the bacteria’s whereas cephalosporin showed increased resistance. However, for uncomplicated community acquired UTI, Nitrofurantoin (oral) and Amikacin (Injectable) can be chosen as first line medication.J MEDICINE JUL 2020; 21 (2) : 93-97